2022
DOI: 10.4103/jpbs.jpbs_626_21
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Abrasion, Sexual Dimorphism, and Anthropometric Tooth Dimension

Abstract: Introduction: The aim of this study was to analyze the anatomic crowns of the maxillary and mandibular dentition concerning the mesiodistal, buccolingual measurements which will be used to establish normative data as a part of comprehensive study being carried out to determine the depth of the cervical abrasion (CA) of the individuals by predicting the CA Index of Treatment Needs (CAITN) score. Materials and Methods: A newly developed instrument termed as CAITN probe wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The maximum number of reported cases of CoVid-19 infection were from partially vaccinated group 50.7% (took only first dose of vaccine) than fully vaccinated group 49.3% among the 280 vaccinated individuals. Similar findings were reported with Ali et al 2022 [ 10 ]; Amit et al 2021 [ 11 ]; Keehner et al 2021 [ 12 ]; Sabnis et al 2021 [ 13 ] and Kandeel et al [ 14 ]. Shahapur et al 2022 [ 8 ] reported the most of the symptomatic patients of infection were suffered with episodes of fever, headache, sore throat, fatigue, cough, and breathlessness.…”
Section: Discussionsupporting
confidence: 88%
“…The maximum number of reported cases of CoVid-19 infection were from partially vaccinated group 50.7% (took only first dose of vaccine) than fully vaccinated group 49.3% among the 280 vaccinated individuals. Similar findings were reported with Ali et al 2022 [ 10 ]; Amit et al 2021 [ 11 ]; Keehner et al 2021 [ 12 ]; Sabnis et al 2021 [ 13 ] and Kandeel et al [ 14 ]. Shahapur et al 2022 [ 8 ] reported the most of the symptomatic patients of infection were suffered with episodes of fever, headache, sore throat, fatigue, cough, and breathlessness.…”
Section: Discussionsupporting
confidence: 88%
“…The buccolingual measurement of each tooth was performed using the CAITN probe [ 12 , 13 ]. The depth of the lesion was measured by placing the probe perpendicular to the long axis of the tooth at the center of the lesion.…”
Section: Methodsmentioning
confidence: 99%
“…The CAITN index was created using data from prior extensive research [16][17][18][19][20] to inform treatment choices. The authors examined 840 teeth from 30 participants, with a mean age of 48.4 years, and with or without cervical abrasions [16,19]. Using a CAITN probe [18], we recorded the buccolingual dimension of each tooth.…”
Section: Development Of the Caitn Indexmentioning
confidence: 99%
“…A mouth mirror was used for withdrawal and better visibility to avoid gingival puncturing in the buccal and palatal minor region of the gingiva, and the bills of the CAITN test were inserted into the deepest part of the cervically scraped spot. Some portion of the tooth is opposite to the long hub of the tooth to record buccolingual measurements [ 19 , 20 ]. The depth of the cervical abrasion may be calculated by comparing the reading on the CAITN probe scale with the mesiodistal and buccolingual measurements of the affected tooth, all of which are standardized.…”
Section: Reviewmentioning
confidence: 99%